Mental Health Approach in Pixar Animated Films: Conceptions from Information Mediation - Laura de Azeredo; Beckman Cavalcante, Luciane de Fátima (Revista Cubana de Información en Ciencias de la Salud, 2025)
Animated films are sources of information that should be used for different purposes and for different audiences. From this perspective, this research aims to analyze how the discussion about mental health is mediated in Pixar Animation Studios films for young and adult audiences. In terms of methodology, the study is qualitative, descriptive and documentary in nature, using six animated films from the studio as the research universe: Toy Story 3, Inside Out, The Incredibles 2, Onward, Soul and Luca. In addition, it was used Laurence Bardin's content analysis technique. Based on the exploration of the films' narratives through the lens of three delimited categories, it was observed that this theme is discussed in animated films in such a way that audiences of different ages can interpret it according to their world views. Therefore, the same narrative can be understood and explored with different levels of depth by both children and adults.